Prevalence of dental caries in male children from 3 to 14 years of age of Bundelkhand region, India - Jain, Arvind; Jain, Vandana; Suri, Sheenu Malik; Jain, R. K. (International Journal Of Community Medicine And Public Health, 2017)
Background: Dental caries is a public health problem in developing countries like India. The problem is dreadful among children particularly of low socio-economic status in rural area. The present study was planned to assess the prevalence of dental caries among children of rural Bundelkhand region. Methods:The present study was conducted in the male children attending the paediatric OPD in Tikamgarh district of Madhya Pradesh. The age group considered for study was from 3 to 14 years of age. Results: The overall prevalence of the dental caries in male children was found to be 82.62% with mean DMFT/dmft to be 3.58 and the prevalence is higher in middle childhood group of 7-10 years (87.09%) as compared to pre-school group including 3-6 years (81.07%) and late childhood group of 11-14 years (75.72%). Conclusions:The study population showed a very high prevalence of 82.62% among male children of Bundelkhand region. It indicates the need for educating the population about the causative factors for dental caries and immediate intervention in the form of dental health education.